A Plasma Clot Lysis Assay Based on the Release of Fibrin Degradation Products: Application to the Diagnosis of Hypofibrinolytic States - Gaussem, Pascale; Gandrille, Sophie; Molho-Sabatier, Pascale; Capron, Loïc; Fiessinger, Jean-Noël; Aiach, Martine (Thrombosis and Haemostasis, 1990)
Using a monoclonal antibody-based assay, we measured the fibrin degradation product release in the supernatant of plasma clots obtained before and after venous occlusion (VO) in 30 patients with definite or suspected vascular thrombosis (19 definite and 2 suspected deep vein thrombosis, 6 recurrent superficial thrombophlebitis, 3 arterial occlusions of lower limbs). tPA and PAI-1 concentrations were determined using ELISA assays; the post-occlusion values were corrected for haemoconcentration. The increase in tPA during VO was correlated with haemoconcentration (r = 0.74), but 3 patients had ineffective VO (<2% increase in proteins). The fibrinolytic response to VO was evaluated using the shortening of the time necessary for the release of 200 μg of fibrin degradation products per mg of fibrinogen (Δ T 200). Two among the 27 patients with effective VO were bad responders with a Δ T 200 <3 h (whereas all the others had Δ T 200 >10 h). These patients had respectively a deficient tPA release (Δ tPA = 1 ng/ml) and an elevated PAI-1 level at rest (33 ng/ml). Several other patients were bad responders in terms of tPA release or of shortening of the euglobulin clot lysis time but they had a normal Δ T 200. This plasma clot test reflects the ability of free tPA to bind to fibrin (the amount of which depends on the level of tPA and PAI-1), and may be useful in the diagnosis of a hypofibrinolytic state.
Keywords: Thrombosis; Plasma clot lysis; Fibrin degradation products